1978
DOI: 10.1111/j.1476-5381.1978.tb07754.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnesium on the Response of Smooth Muscle to 5‐hydroxytryptamine

Abstract: The responses to 5‐hydroxytryptamine (5‐HT) of rabbit isolated mesenteric artery and vein and longitudinal smooth muscle of guinea‐pig ileum were examined in Krebs solution containing 0, 1.2 or 2.4 mm Mg2+. When the concentration of Mg2+ was raised the spontaneous contractile activity of rabbit mesenteric vein was depressed. The responses to 5‐HT in rabbit mesenteric artery and vein and guinea‐pig ileum were greater in the absence of Mg2+. The initial fast component of 5‐HT‐induced contractions in rabbit mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Recently, in single myocytes from frog ventricle, the site of interaction between Mg 2+ and Ca 2+ was identified as the Ca 2+ inward current that is dependent on phosphorylation by cyclic adenosine monophosphatase [31]. Sec-Kisters/Körner/Louwen/Witteler/Jackisch/ Zidek/Ott/Westermann/Barenbrock/Rahn ond, changes in the extracellular Mg 2+ concentration induced inverse changes in the Ca 2+ content of vascular smooth muscle and in exchangeable Ca 2+ [31][32][33]. These findings suggest competition between Mg 2+ and Ca 2+ for intracellular binding sites as a further mechanism for Mg 2+ -induced vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in single myocytes from frog ventricle, the site of interaction between Mg 2+ and Ca 2+ was identified as the Ca 2+ inward current that is dependent on phosphorylation by cyclic adenosine monophosphatase [31]. Sec-Kisters/Körner/Louwen/Witteler/Jackisch/ Zidek/Ott/Westermann/Barenbrock/Rahn ond, changes in the extracellular Mg 2+ concentration induced inverse changes in the Ca 2+ content of vascular smooth muscle and in exchangeable Ca 2+ [31][32][33]. These findings suggest competition between Mg 2+ and Ca 2+ for intracellular binding sites as a further mechanism for Mg 2+ -induced vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Mg 2+ can produce not only relaxation per se, but is also capable of modulating the vascular reactivity to a large number of substances such as potassium, prostaglandin F 2· , noradrenaline and 5-HT [26]. In a study performed by Turlapaty and Altura [27], it was clearly demonstrated that the calcium movements in the aorta and portal veins of the rat are influenced by extracellular Mg 2+ concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin receptor activity is altered by changes in levels of ionized Mg +2 [31,32] and vasoconstriction induced by serotonin can be effectively blocked by pretreatment with Mg +2 [33]. Experimental Mg +2 deficiency leads to generation and release of substance P [34] which is thought to act on sensory fibers and cause the pain in headache [35].…”
Section: Discussionmentioning
confidence: 99%